Resin related enterocolitis: An underreported co-occurrence - Sonali Mishra; Gajendra K. Yadav; Rohit Gupta; Arvind Kumar (Wolters Kluwer Medknow Publications, 2024)
Medication resins are often encountered in gastrointestinal biopsy specimens of patients being treated for renal compromise. As important as they are for the electrolyte equilibrium of the patients, they often come with a cost of fatal but reversible damage to the gastrointestinal tract. This often manifests as inflammatory bowel disease in the affected individuals. This misleading manifestation coupled with the lack of patient history further masks resin-related colitis from a pathologist's eyes. Through this report, we convey how meticulous history-taking, representative endoscopic sampling, and recognition under the microscope are vital for timely reporting in conditions like this.